2005
DOI: 10.1111/j.1365-2958.2005.04747.x
|View full text |Cite
|
Sign up to set email alerts
|

A symbiosis expressed non‐ribosomal peptide synthetase from a mutualistic fungal endophyte of perennial ryegrass confers protection to the symbiotum from insect herbivory

Abstract: SummaryWhile much is known about the biosynthesis of secondary metabolites by filamentous fungi their biological role is often less clear. The assumption is these pathways have adaptive value to the organism but often the evidence to support this role is lacking. We provide the first genetic evidence that the fungal produced secondary metabolite, peramine, protects a host plant from insect herbivory. Peramine is a potent insect feeding deterrent synthesized by Epichloë/ Neotyphodium mutualistic endophytes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
251
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(269 citation statements)
references
References 77 publications
7
251
0
1
Order By: Relevance
“…Recently, it was shown that peramine is produced by an endophyte-specific two-module nonribosomal peptide synthetase (perA) and that an Epichloë festucae mutant deleted for perA lacks detectable levels of peramine (Tanaka et al, 2005). It was also shown that plant material containing this mutant endophyte was as susceptible to Argentine stem weevil feeding as endophyte-free plants, demonstrating unambiguously that peramine confers resistance to this insect.…”
Section: Biological Implications Of Identified Metabolitesmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, it was shown that peramine is produced by an endophyte-specific two-module nonribosomal peptide synthetase (perA) and that an Epichloë festucae mutant deleted for perA lacks detectable levels of peramine (Tanaka et al, 2005). It was also shown that plant material containing this mutant endophyte was as susceptible to Argentine stem weevil feeding as endophyte-free plants, demonstrating unambiguously that peramine confers resistance to this insect.…”
Section: Biological Implications Of Identified Metabolitesmentioning
confidence: 97%
“…Endophyte-free perennial ryegrass was obtained as described by Tanaka et al (2005). A 2 3 3 factorial design was applied with endophyte-infected (E1) and endophyte-free (E2) plants, and three tissue types, namely, immature leaf, blade, and sheath.…”
Section: Experimental Design and Samplingmentioning
confidence: 99%
“…-Genes involved in the peramine, indole-diterpene, and ergot alkaloid pathways (Tanaka et al 2005;Young et al 2006;Fleetwood et al 2007) were identified in E. hybrida Lp1 using the BLASTn function of Geneious 8.1.5 (Kearse et al 2012). Alkaloid production by E. hybrida Lp1, E. festucae var.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary metabolite genes and alkaloid production.-To profile the secondary metabolites of E. hybrida Lp1, genomic reads were mapped against genes previously characterized as being responsible for peramine, indole-diterpene, and ergovaline biosyntheses (Tanaka et al 2005;Young et al 2006;Fleetwood et al 2007;Schardl et al 2013a). Assembled genes have been deposited in GenBank (SUPPLEMENTARY TABLE 1; see also Schardl et al 2013b for additional accessions of these genes).…”
Section: −4mentioning
confidence: 99%
“…Of these, the ergot alkaloids and tremorgenic lolitrems cause neurotoxic effects on grazing or granivorous vertebrates (Steyn and Vleggaar 1985;Bacon et al 1986). Peramine is an insect feeding deterrent and protects perennial ryegrass from the Argentine stem weevil, Listronotus bonariensis, a highly destructive insect pest in New Zealand (Rowan and Latch 1994;Tanaka et al 2005). Lolines are potent insecticidal and anti-aphid agents, not being implicated in any mammalian toxicoses (Jackson et al 1996;Wilkinson et al 2000).…”
Section: Agricultural Aspects: Endophytic Insecticides Vs Tremorgenimentioning
confidence: 99%